In our name - Welsh, Brian; Froggatt, Joanne; Raido, Mel; Wilkinson, Chloe-Jayne (Artificial Eye, 2011)
Suzy's a British soldier, born and bred, but fitting back into civilian life after fighting in Iraq isn't easy. Haunted by the responsibility she feels for the death of an Iraqi child, she becomes obsessed with the safety of her own daughter, feeling the need to protect her against a threat that doesn't seem to exist. As Suzy's paranoia builds, her behaviour becomes more and more erratic, until finally, she puts her own child in serious danger. (IMDb) ; en